Perbandingan Perlindungan Hak Perempuan Pasca Perceraian Dalam Fikih Islam dan kompilasi hukum islam (KHI) - husna, arinal (Maliki Interdisciplinary Journal, 2026)
Divorce is one of the events in married life that has a significant impact, especially on women. Although divorce is permitted in Islam, it is still considered an undesirable act if there is still a way to maintain the marriage. Therefore, when divorce truly occurs, Islam continues to give special attention to the rights of women so that they are not simply abandoned after the marital relationship ends. These rights include financial support during the iddah period, mut’ah, housing, and protection for children who are under their care. In Indonesia, similar protection is also regulated in the Compilation of Islamic Law (KHI), which serves as a guideline for the Religious Courts. This paper compares the forms of protection for women’s rights after divorce according to Islamic jurisprudence and the Compilation of Islamic Law (KHI), while also examining the extent to which both regulations provide a sense of justice and legal protection for women.